Education of Marginalized Groups: A Study on the Religiosity of Street Children in the Regency of Jember - Wibowo, Safrudin Edi; Elhady, Aminullah; Tamam, Badrut; Fathiyaturrahmah, Fathiyaturrahmah (Ulumuna, 2022)
Street children’s rights are often neglected, including their right to receive religious education.This study examines the dimensions of religiosity of street children and the influencing factors, as well as the appropriate mentoring method for them. Data were gathered through observations, in-depth interviews, and focused group discussions were analyzed, and the results indicate that family, educational institutions, and social environment influence street children’s religiosity. This study is built upon the researchers’ experience carrying out a religious mentoring program for street children. The study suggests that street children maintain a sense of religiosity and its various dimensions. Formulating religious mentoring programs that align with the dimensions of religiosity is recommended.